Analisis Pengaruh Harga dan Kualitas Produk Terhadap Loyalitas Konsumen dengan Kepuasan Konsumen Sebagai Variabel Intervening untuk Sepatu Sepak Bola Merek Specs : Studi Empirik Pada Komunitas Sepak Bola Di Kabupaten Bogor - Pratama, Yunan Bayu; Thalib, Supriadi; Miranda, Agustinus (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to analyse the influence of price and product quality on consumer loyalty, with consumer satisfaction as an intervening variable, for the Specs brand football shoes (an empirical study in the football communities of Kabupaten Bogor). The research utilises non-probability sampling with a purposive sampling method, involving 120 respondents, examining the impact of price and product quality on consumer loyalty, with consumer satisfaction as the intervening variable (an empirical study within football communities in Kabupaten Bogor). The research employs Structural Equation Modeling analysis. The results of the study indicate that (1) Price significantly influences consumer satisfaction, (2) Product quality significantly influences consumer satisfaction, (3) Price does not affect consumer loyalty, (4) Product quality significantly influences consumer loyalty, (5) Consumer satisfaction significantly influences consumer loyalty, (6) Price significantly influences consumer loyalty through consumer satisfaction, (7) Product quality significantly influences consumer loyalty through consumer satisfaction.